The Psycho-biophysical Modeling of the some Stress Parameters - Janos Vincze; Gabriella Vincze-Tiszay (Technium Social Sciences Journal, 2020)
The human organism is a biophysical system. Stress represents a normal reaction of the organism which appears as a response to an aggression situation which requires an unusual and quick adaptation effort from the organism. Stress is a state of putting in alert, of mobilizing the forces of the organism in the occasion of an event which requires, in order to be kept under control, a big amount of energy in a very short time. This alert state or action preparation translated through physical and psychological manifestations. In higher-level living organisms the following forms of regulation are known: biological, nervous, hormonal, humoral and immune regulation. In the case of humans, psychic regulation also appears due to the existence of psychic activity. We study only two forms of the stress: fear and death. We present different biophysical modeling aspects. The stress in the human organism is a perturbation. This perturbation is regulates by negative feedback.